"It Lets Me Fight the Bad Guys": An Exploration Into the Factors Predicting Enjoyment of Violent Video Games. Issue 1 (1st January 2019) - Riddle, Karyn; Tay, Swee Kiat; Wu, Jiaxi
Abstract : In an exploratory survey that sampled video gamers, participants were asked to indicate why they enjoy playing their favorite video game. On the basis of ESRB ratings, we compare those whose favorite game is violent to those whose favorite game is nonviolent. Consistent with self-determination theory, the findings suggest need for autonomy and competence are important motivating factors. However, the findings also suggest fans of violent games differed from fans of nonviolent games in the degree to which arousal, liking violence, playing the vicarious hero, and playing the vicarious villain drive enjoyment. Furthermore, being able to play the hero and "fight bad guys" was a significant predictor of enjoyment of violent games. Implications for self-determination theory and theories of media enjoyment are discussed.